PENDIDIKAN KARAKTER â€˜TIDAK MEROKOKâ€™ DI SEKOLAH MUHAMMADIYAH DI KOTA KRETEK - Anita Aisah; Usfur Ridha (State Islamic University (UIN) Ar-Raniry, 2017)
Educating students not to smoke is one of the goals of character education in schools. This study aimed to illustrate how character education â€œdoes not smokeâ€ in muhammadiyah schools in the Kudus City. The researcher selected the Muhammadiyah school and took place at Kudus, for various reasons. The Kudus City is known as the City of Kretek, while the Assembly of Tarjid and Tajdid Muhammadiyah issued illegal laws for people who smoke. In addition, the cigarette industry in Kudus also supports school facilities and infrastructure. This makes the researchers want to know the picture of non-smoking education at the Muhammadiyah Kudus School. The subjects were PDM cadres in Kudus City, Muhammadiyah Teachers and Muhammadiyah High School Principals in Kudus. Data were retrieved by using observation and interview technique. The results of this study were (1) Some teachers have a dilemma to convey strict smoking ban in schools because Cigarette industry has a big role in the development of Muhammadiyah schools; (2) The punishment for students who smoke remains strictly enforced in all three schools; (3) Educators are trying to be role models through not showing smoking behavior in schools; (4) The School Party does not cooperate with parents to prohibit students smoking outside school; (5) There is no difference in the smoking ban regulations in the three Muhammadiyah Schools before and after the Fatwa Haram issued by Majelis Trajih and Tajdid Muhammadiyah Central Executive.